The First MSC Missionary Work In Merauke - Simon Takahanem Kaize (Fakultas Teologi, Universitas Sanata Dharma, 2025)
The arrival of the Missionaries of the Sacred Heart (MSC) in Merauke in the early 20th century brought significant changes to the Marind community, both in the religious, educational and social fields. This article discusses how the first MSC missionaries introduced the image of God to the Marind tribe in Merauke. Using a critical historical approach, this research highlights how the missionaries introduced the image of God in the light of the Catholic faith in accordance with the theological truths of the Council of Nicea (325 AD). The Council affirmed that God is one in essence (ousia), but three in person (hypostasis), namely God the Father, God the Son (Jesus Christ), and God the Holy Spirit. In the context of the Marind tribe, it is God who is close to humans, and God who brings social transformation. In the Marind belief tradition, the image of God does not always refer to the monotheistic concept as in Abrahamic religions, but rather to animistic and cosmological belief systems that connect humans with ancestors and nature. Marind religious concepts such as Dema, respect for ancestors, and a close relationship with nature serve as a bridge in the proclamation of the Catholic faith. This study shows that the first MSC missionary mission was not just the spread of religion, but also a social transformation that still respects local cultural values and the continuity of the MSC mission in Merauke and the challenges of evangelization in the modern era.